English Students’ Perceptions of the Use of Social Media in English Language Learning - Amalia, Nissa; Zuhad Ahmad (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
The objective of this research is to explore the perceptions of students majoring in English Education at Universitas Muhammadiyah Prof. Dr. Hamka towards the use of social media in English language learning. Using a descriptive qualitative method, this research involved 40 final semester students who actively use social media as a learning tool. The results showed that social media, such as YouTube and TikTok, contributed significantly to improving students' English skills, especially in the aspects of listening and reading. The study concludes that social media has great potential as an effective English language learning tool, provided that these challenges can be overcome through structured strategies. The findings provide insights for educators in integrating social media into the curriculum to create a more dynamic and responsive learning environment.